Dye Sensitized Solar Cells with Low Cost Carbon Nanotubes Electrodes - F. M. Al-Marzouki; S. Abdalla; S. Al-Ameer (Advances in Materials Science and Engineering)
Dye sensitized solar cells (DSSCs) are very sensitive to electrodes, due to either high cost or easy corrosion problems. To minimize these factors, we present DSSCs with cheap carbon nanotubes as counter electrodes. In addition, we suggest replacing the electrolyte (in typical DSSCs) with a solid film of powdered CsSnI3. The electrical behavior (I-V characteristics) of the proposed device has been measured for different shading conditions. In the light of a theoretical model based on the presence of two diodes, the experimental data have been explained, taking into account a new equivalent circuit for the DSSC. These DSSCs may receive different levels of sun radiation, which stimulates the study of partial shading; so, we have studied the effect of different shadow rates on the solar conversion efficiency of a unit of 4-W-connected DSSCs. The validity of the present model has been examined by fitting it into I-V characteristics at different shading rates.